Dyeing of silk with isolated bixin based orange yellow natural dye: Kinetic, thermodynamic and colorimetric aspects - Muhammad Ibrahim; Bisma; Shahid Adeel; Al Mojnun Shamim; Mohammad Khajeh Mehrizi; Muhammad Imran; Muhammad Asif Tahir; Rony Mia (Results in Engineering)
Greener products, particularly natural colorants have attracted the globe due to the spread of toxic awareness of synthetic dyes. This study investigates the use of bixin, a natural dye extracted from annatto seeds (Bixa orellana), as a sustainable alternative for dyeing silk fabrics. The objectives were to optimize the extraction and dyeing processes, evaluate the effects of mordants, and assess the biological activities of the dyed fabrics. Microwave-assisted extraction (MW) was employed to improve dye yield, with optimal conditions determined using response surface methodology through formulated central composite design under ANOVA analysis. Dyeing parameters were optimized, and the effects of eco-friendly mordants (Al, Fe salts, pomegranate, and myrobalan) were evaluated. After experiments, it has been found that 30 mL extract of 8 pH after MW treatment upto 4 min, if used to dye silk at 55 °C for 55 min in presence of 1 g/100 mL of salt, highest yield can be obtained. Spectral analysis has been performed for morphological and chemical changes in extract and fabrics before and after irradiation respectively. Under these conditions, 0.5 % pre and 0.5 % as post Al chemical mordant and 1.5 % pre and 2 % as post pomegranate bio-mordant has potential to developed colorfast shades. Dyeing kinetics followed a pseudo-second-order model, while the Langmuir isotherm best described the adsorption process. The dyed silk fabrics exhibited notable antibacterial activity against S. aureus and E. coli. The annatto extract showed up to 82.09 % antioxidant activity. As a result, this study demonstrates the potential of annatto-based bixin as an eco-friendly alternative to synthetic dyes, offering both coloration and functional properties to silk fabrics.